Assessing the distributional impact of lowering the value-added tax rate for standard-rated items in Tanzania and options for recouping revenue losses - Elineema Kisanga; Vincent Leyaro; Wahabi Matengo; Michael Noble; Helen Barnes; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper explores the distributional impact of lowering the value-added tax rate for standard-rated items in Tanzania Mainland. Using a static tax-benefit microsimulation model- TAZMOD-which is underpinned by data derived from the Household Budget Survey 2017/18, reductions in value-added taxes from 18 per cent to 17 per cent and 16 per cent are simulated. The revenue losses and impact on poverty are estimated. The rules for direct taxes are then modified in order to identify ways in which the revenue loss caused by the lowering of the standard rate of value-added taxes can be recouped.
Keywords: H23; H53; 330; value-added tax; microsimulation; redistribution; revenue; Tanzania